STRATEGY FOR THE INSTITUTIONAL TRANSFORMATION OF REGIONAL RESEARCH AND INNOVATION IN STRENGTHENING DEVELOPMENT PLANNING IN NORTH MINAHASA REGENCY - Muhammad Busthomi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
This study will examine the factors that serve as drivers and challenges for BRIDA North Minahasa Regency in the institutional transformation process, as well as the strategies implemented by BRIDA North Minahasa Regency to ensure the institutional transformation process runs optimally. This research uses a qualitative method, employing interviews and questionnaire completion with respondents who consist of officials from 1) BRIDA North Minahasa Regency, 2) North Minahasa Regional Development Planning Agency, and 3) the Deputy for Regional Research and Innovation – BRIN, along with document review. The results show that the challenges in the institutional transformation process lie in four main aspects: leadership, institution/organizational structure, human resources, and budget. The strategies used by BRIDA North Minahasa Regency in the transformation process are: 1) Encouraging the Master Plan and Roadmap for the Advancement of Science and Technology in the Region (RIPJPID) as a mandatory document to be considered in the preparation of the North Minahasa Regency Regional Medium-Term Development Plan (RPJMD) and the Strategic Plan (RENSTRA) documents of regional apparatus through the establishment of a North Minahasa Regent's Regulation; 2) Promoting the implementation of evidence-based policy in the entire process of regional development planning and implementation by accelerating the internalization of evidence-based policy principles to other regional apparatus organizations; 3) Providing assistance to the community to encourage a research and innovation culture to become a new culture in North Minahasa through breakthrough programs and activities that directly address community needs; and 4) Strengthening BRIDA's role as an orchestrator in building the research and innovation ecosystem in North Minahasa Regency through cross-sector collaboration.